The Beginnings of Polish Musicology - Sieradz, Małgorzata (2020)
The book presents the history of the only strictly scientific Polish musicological periodical Kwartalnik Muzyczny. It shows how the editorial board of the periodi-cal met with true approval and harsh criticism. The subject allows the author to present the beginnings of Polish musicology and its evolution through three epochs: the late partitioning period, the interwar period of Poland's independ-ence, and the early years after the Second World War...